Pengaruh Alasan Positif Dan Negatif Terhadap Sikap Dan Niat Pembelian Konsumen Gen Z Dalam Belanja Online: Studi Komparatif Produk Search Goods Dan Experience Goods - lily Wijaya; Nathania Trinita Shallomita Pandey; Keisya Engguenia Kawuwung; Charlesyn; Mahdiyah Malak; Angeline Virginia Gonardo; Monalisa (Jurnal Online Manajemen ELPEI, 2026)
This study aims to analyze the influence of positive reasons (reasons for) and negative reasons (reasons against) on attitudes and purchase intentions among Generation Z online shoppers using the Behavioural Reasoning Theory (BRT) framework. The study also compares how these reasons operate across different product categories, namely search goods and experience goods. Data were collected through a survey of 200 Gen Z respondents who actively engage in online shopping. The data were analyzed using Partial Least Square–Structural Equation Modeling (PLS-SEM). The results indicate that positive reasons have a positive and significant effect on attitude, with a path coefficient of 0.607, making it the strongest determinant of consumer attitude. Negative reasons also significantly influence attitude, although with a much weaker effect (β = 0.090). Furthermore, attitude significantly and strongly affects purchase intention, with a path coefficient of 0.709. The R-square results show that 43.1% of the variance in attitude is explained by positive and negative reasons, while 50.3% of the variance in purchase intention is explained by attitude. These findings support BRT’s central proposition that reasons serve as rational explanations that shape attitudes before influencing behavioral intentions. Comparative analysis between search goods and experience goods further suggests that positive reasons remain the dominant factor across both product types. Overall, this research confirms that Behavioural Reasoning Theory is an appropriate framework to understand Gen Z’s decision-making processes in online shopping and provides practical implications for e-commerce businesses to strengthen reasons for in digital marketing strategies.